Representation of Women in Asians Family in the Film Crazy Rich Asians - Purwani, Made Ijya Githa; Joni, I Dewa Ayu Sugiarica; Suryawati, I Gusti Agung Alit; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2024)
Crazy Rich Asians is one of the movies that portrays the role of women in an Asian family. Patriarchy is still dominant in many Asian countries, women are often depicted as housewives, dependent on men, unable to make important decisions, and acting passively. This study uses Roland Barthes's semiotic theory in finding denotative meaning, connotative meaning and myths by analyzing signs in the Crazy Rich Asians movie. The results of this study show that Crazy Rich Asian displays signs that represent women in an Asian family; where women contentedly take up the role of housewives, they are able to work in public sectors but choose not to and women are not to make important decisions which will affect the rest of the family.